In Vitro Conservation and Metabolite Profiling of Patchouli (Pogostemon cablin Benth.): Hormonal Effects on Callus and Volatile Oil Preservation - Amboupe, Dewi Sartika; Sa’diyah, Jamilatus; Anggita, Sri Ayu (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2025)
Patchouli (Pogostemon cablin Benth.) is a significant tropical bioresource known for its essential oil, which possesses high ethnobiological and economic value but cannot yet be synthetically produced. This study aims to establish an in vitro conservation framework and evaluate the preservation of secondary metabolites (volatile oil) within callus cultures. Leaf explants were cultured on Murashige and Skoog (MS) media supplemented with various combinations of 2,4-D and BAP: 1 ppm BAP (W1), 1 ppm BAP + 1 ppm 2,4-D (W2), 1 ppm BAP + 2 ppm 2,4-D (W3), 2 ppm BAP + 1 ppm 2,4-D (W4), and 2 ppm BAP + 2 ppm 2,4-D (W5). The results indicated that W1 (1 ppm BAP without 2,4-D) was the most effective treatment for sustainable biomass production, achieving a 75% growth rate, the fastest induction time (6 days), and the highest fresh weight (0.1364 g). Thin Layer Chromatography (TLC) profiling confirmed that the in vitro callus successfully preserved volatile oil components identical to the mother plant, as evidenced by purple spots at Rf values of 0.75 and 0.95. Although alkaloids and flavonoids were not detected due to the cellular dedifferentiation phase, the consistent presence of volatile oils demonstrates the potential of in vitro systems for the conservation and sustainable management of tropical aromatic plant metabolites.